PENGARUH JOB INSECURITY DAN STRES KERJA TERHADAP TURNOVER INTENTION PADA MELASTI BALI BEACH RESORT - Ayu Asri Wulandewi, Ni Made; Wijaya, Bagus Arya (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2023)
The purpose of this study is to examine the impact of job insecurity and job stress on the intensity of leaving work. The population in this study included all Melasti Bali Beach Resort employees, totaling 79 people, and the sample in this study consisted of 65 respondents. The sampling method in this study used a census technique. Data were collected through observation, interviews, distribution of questionnaires and documentation where a five-point Likert scale was used to measure 24 questions. The analysis technique used is classic hypothesis testing, multiple calculations, determination calculations, simultaneous tests (F test) and individual tests (t test). Based on the test, the results of the analysis show that there is a direct and real relationship simultaneously and separately between job insecurity and work stress on turnover intention at Melasti Bali Beach Resort. It is recommended to reduce turnover intentions, companies are advised to reduce the level of job insecurity and work stress on employees.